Effect of mother–infant pair's latch-on position on child's health: A lesson for nursing care - Joshi, Harshdeep (J Family Med Prim Care, 2016)
BACKGROUND: Effective breastfeeding is a function of the proper positioning of mother and baby and attachment of child to the mother's breast. Positioning of the baby's body is important for good attachment and successful breastfeeding. The study was planned to assess mother–infant pair latch on position and its impact on health status of the child. MATERIALS AND METHODS: It was community-based cross-sectional study conducted among 1267 children between age group of 0–24 months in the urban and rural field practice areas of the Department of Community Medicine, Maharishi Markandeshwar Institute of Medical Sciences and Research, Mullana, Ambala, Haryana. A self-designed semi-structured questionnaire along with the WHO criteria for assessment of correct latch on position was used in this study. RESULTS: Out of 1267 mothers, only 29.9% mothers initiated breastfeeding within 1 h of delivery. Mothers who had high parity had better positioning scores as compared to mothers with low parity. About 83.7% mothers who had parity >2 had excellent scores as compared to those mothers having one child or two children. About 56.8% and 62.7% children who suffered from diarrhea and acute respiratory infection (ARI), respectively, had mothers with poor positioning and this difference was statistically significant (P < 0.001). CONCLUSION: It was concluded that mothers who had higher parity had better positioning and attachment scores and also mothers with excellent positioning scores, their children suffered less from diarrhea and ARI. Each mother should be observed for mother's and infant's positioning and attachment at the onset of breastfeeding and if needed given counseling on correct positioning and attachment.